1990
DOI: 10.1111/j.1558-5646.1990.tb05946.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Phenotypic Differentiation Among Bottleneck Lines of the Housefly

Abstract: Abstract.-Multivariate phenotypic differentiation in eight morphometric traits was examined in bottleneck lines of the housefly initiated with one, four, or 16 pairs offties from a natural outbred population. Differentiation was assessed using a Mahalanobis' distance metric in units of additive genetic variance and covariance estimated from the ancestral population (i.e., generalized genetic distance). This distance metric was partitioned into contributions ofsize and shape to total distance. Bottleneck lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…A final caveat is that the G matrix itself may have changed during the past 4000 years, because of a founder effect occurring during colonization and/or selection associated with an island environment. Population bottlenecks are expected to affect G matrix structure, although in an unpredictable manner and only if the size of the founder population is very small (Bryant & Meffert, 1990;Phillips et al, 2001). A strong bottleneck is an unlikely scenario here because of the proximity of Heron Island to the mainland (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A final caveat is that the G matrix itself may have changed during the past 4000 years, because of a founder effect occurring during colonization and/or selection associated with an island environment. Population bottlenecks are expected to affect G matrix structure, although in an unpredictable manner and only if the size of the founder population is very small (Bryant & Meffert, 1990;Phillips et al, 2001). A strong bottleneck is an unlikely scenario here because of the proximity of Heron Island to the mainland (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction has been tested and confirmed in a wide variety of organisms and experimental systems. (18,(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) Recently, a rigorous molecular genetic study in yeast (56) has shown that the evolvability (ability to generate selectable phenotypic variation) of a gene depends upon the number of other genes whose activity affects it and the number of different regulatory sites that are associated with the gene. These molecular studies in yeast confirm the special importance of the new mutations or recombinants that accumulate in the flush phase in genes or gene complexes that are part of an epistatic system.…”
Section: Evidence For the Gtff Mechanismsmentioning
confidence: 99%
“…Small populations of invading organisms may carry only a fraction of the genetic diversity of their source populations. Experimental studies with houseflies have shown that such 'bottlenecking' may alter genetic relationships among traits that could lead to differentiation along evolutionary trajectories less accessible to the original populations (Bryant & Meffert, 1990). Stone and Sunnucks (1993) conducted a survey of 39 populations of cynipid gallwasps that have tracked their oak host as it has been transplanted westward across Europe over the past 300400 years, in an increasingly patchy distribution.…”
Section: Pp-pp H-pp H-h H-bb Bb-bbmentioning
confidence: 99%